School Website Development for Parental Information Access: Pengembangan Website Sekolah untuk Akses Informasi Orang Tua - Fauziyyah, Ayu Faza; Wahyudin, Wahyudin; Rahayu, Ayu Puji (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: The rapid advancement of information technology has reshaped information management and communication practices within educational institutions, including primary schools. Specific Background: At SDIT Persis 99 Rancabango, school information for parents has been disseminated through fragmented and conventional channels, resulting in unstructured data and limited traceability. Knowledge Gap: Previous studies predominantly positioned school websites as promotional or one-way communication tools, leaving limited empirical evidence on their role as centralized information systems tailored to sustained parental access. Aims: This study aimed to develop a school information system based on a website using Google Sites to provide structured, integrated, and continuously accessible information for parents. Results: Using the ADDIE development model, the website was validated by media and content experts with feasibility scores exceeding 90%, received highly positive parental responses, and demonstrated a statistically significant increase in parental information access based on pretest–posttest analysis. Novelty: This study positions Google Sites as a practical platform for developing a centralized school information system specifically oriented toward parental information needs in primary education contexts. Implications: The findings provide empirical and practical contributions for elementary schools with limited resources in adopting centralized, user-friendly digital information services to support transparent and structured school–parent communication. Highlights • Centralized School Information Reduced Fragmented Communication Channels• Google Sites Supported Structured Parental Information Access• ADDIE-Based Development Achieved High Expert Validation Scores Keywords School Information System; School Website; Google Sites; Parental Information Access; ADDIE Model